Revision of the Lucanus boileaui group and notes on L . takeoi Adachi, 2020 from the L . maculifemoratus group (Coleoptera: Lucanidae: Lucaninae) - Qi, Zhi-Hao; He, Hao; Su, Rong-Xiang; Ai, Hong-Mu; Song, Hai-Tian (Zootaxa, 2023)
A new stag beetle is described from Yunnan Province, China: Lucanus jiaozishanus Qi, He, Su & Song, new species. It is the third species of the L. boileaui group which are distributed only in Southwestern China and Northeastern Myanmar. The differences of the new species with the more related taxa (L. boileaui Planet, 1897, L. ludivinae Boucher, 1998 and L. takeoi Adachi, 2020) are discussed. A new synonymy, L. bidentis Schenk, 2013 = L. boileaui, is proposed. Keys to males and females of the L. boileaui group are provided. The variation of males, the female and the host plant of L. takeoi (L. maculifemoratus group) are illustrated for the first time.